PENGETAHUAN DENGAN SIKAP IBU HAMIL PRIMIGRAVIDA TENTANG TANDA BAHAYA KEHAMILAN - Nurmaliza, Nurmaliza; Desmariyenti, Desmariyenti (Poltekkes Kemenkes Pontianak, 2024)
The number of maternal deaths collected from family health program records at the Ministry of Health increases every year. In 2021 there were 7,389 deaths in Indonesia. This number shows an increase compared to 2020 of 4,627. Pregnancy danger signs are signs that indicate dangers that may occur during pregnancy or the antenatal period, which if not reported or detected could lead to maternal death. Pregnant women need good knowledge about danger signs in pregnancy. If pregnant women know about the danger signs in pregnancy, mothers can plan their pregnancy well and immediately go to a health worker if it is a high-risk pregnancy. The aim of this research is to determine the relationship between primigravida pregnant women's knowledge about the danger signs of pregnancy in the working area of the Pratama Afiyah Pekanbaru clinic in 2023. This type of research is quantitative with a cross sectional research design. The population of this study was 85 people with a sample of 70 respondents. Sampling used a non-probability sampling technique using a purposive sampling method. Data processing was carried out univariately and bivariately using the Chi-square test. From the research results, a P - value < α was obtained, namely (0.000 < α 0.5). So Ho is rejected and Ha is accepted, meaning that there is a relationship between knowledge and the attitude of primigravida pregnant women regarding the danger signs of pregnancy in the Pratama Afiyah Pekanbaru Clinic working area in 2023. It is hoped that the research site in the Pratama Afiyah Pekanbaru Clinic Working Area will be able to increase education and socialization about the signs. danger in pregnancy